The effect of synthetic polyethylene fiber on the strain hardening behavior of engineered cementitious composite (ECC) - Said, S.H.; Razak, Hashim Abdul (Elsevier, 2015)
This research investigated the effects of polyethylene (PE) fibers on the toughness and compressive and flexural strengths of engineered cementitious composite (ECC) cubes and slabs. In particular, this study discussed the reinforcing index (R.I.) as the main parameter. Tests were conducted in direct tension to evaluate the strain-hardening behavior of ECC with different PE fiber contents. Flexural toughness was also assessed following the ASTM C1018 procedure and post-cracking strength technique (PCSm). Results showed that the compressive strength linearly decreased with the increase of the reinforcing index, which in turn decreased the first crack load and significantly increased the ultimate load and failure deflections, and the ultimate strength of slabs. The toughness indices 120 to I-100 significantly increased with the increase in reinforcing index and even exceeded the considered limitations. Based on the observed results, a new definition for the ECC PE was proposed as an extension to the definition given in ASTM C1018. All the residual strength factors increased when the reinforcing index increased, indicating a higher amount of the retained strength. Similarly, the retained strength had a higher amount when the PCS24 values increased with increase in the reinforcing indices. (C) 2015 Elsevier Ltd. All rights reserved.